2007
DOI: 10.1017/s1743921308015627
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Three Stars: Stability Limit

Abstract: The problem of three stars arises in many connections in stellar dynamics: three-body scattering drives the evolution of star clusters, and bound triple systems form long-lasting intermediate structures in them. Here we address the question of stability of triple stars. For a given system the stability is easy to determine by numerical orbit calculation. However, we often have only statistical knowledge of some of the parameters of the system. Then one needs a more general analytical formula. Here we start wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The three-body problem is an old topic in celestial mechanics, with wide astrophysical applications in the Solar system and beyond (Valtonen et al 2008;Innanen et al 1997;Holman et al 1997). Hierarchical triple systems are systems in which an inner binary orbits a more distant object on an outer orbit, with some mutual given inclination between the inner and outer orbits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-body problem is an old topic in celestial mechanics, with wide astrophysical applications in the Solar system and beyond (Valtonen et al 2008;Innanen et al 1997;Holman et al 1997). Hierarchical triple systems are systems in which an inner binary orbits a more distant object on an outer orbit, with some mutual given inclination between the inner and outer orbits.…”
Section: Introductionmentioning
confidence: 99%
“…The general equations of motion of the three-body problem cannot be solved analytically (Valtonen & Karttunen 2006), however secular averaging analysis can be used to describe a wide range of cases. For hierarchical systems, pioneering works of Lidov (1962) and Kozai (1962) have shown that the torque of the outer binary can induce significant quasi-periodic oscillations in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of two stability criteria were tested against the numerical results for the fraction of escaping stars shown in Figure 1. These being the MSC discussed in the previous section and the stability criterion from Valtonen et al (2008) which Zhuchkov et al (2010) found to be the most accurate stability criterion of those they tested. Orbital inclination effects are included in the Valtonen et al (2008) stability criterion, however there is no treatment of the eccentricity of the inner orbit (ei).…”
Section: Testing Stability Of Inclined Systemsmentioning
confidence: 99%
“…The stability criterion used in Aarseth (2003) does not include any inclination dependence and is not accurate for the high mass ratios in the galaxy-GC system. Therefore in Section 3 we compare the Mardling stability predictions and the stability criterion of Valtonen et al (2008) to numerical experiments of inclined orbits.…”
Section: Introductionmentioning
confidence: 99%
“…The authors obtained the family of orbits, and according the criterion χ 2 , the orbital period of the best solution is equal to 4000 years. The decay probability of this triple system was calculated by numerical simulations (see , by the criteria of Aarseth (Aarseth 2003) and of Valtonen et al (Valtonen 2008). For e=0.1 the decay probability is less than 2%; for e=0.39 maximal values of the decay probabilities are following: 15% (simulations), 26% (Aarseth), 29% (Valtonen).…”
Section: T Tauri=wds 04220+1932=hip 20390mentioning
confidence: 99%